Kombinasi Terapi Relaksasi Otot Progresif dan Genggam Jari Menurunkan Nyeri Sendi pada Lansia - Fajarina Lathu Asmarani; Adi Sucipto; Indrianingsih (HEALTH CARE: JURNAL KESEHATAN, 2023)
The number of people with joint pain in the world reaches 355 million. The prevalence of joint pain in the elderly comes from 55-64 years aged group is 15.5%, age 65-74 years as much as 18.6%, and age 75 years and over as much as 18.9%. The elderly in Kebonharjo Village reported joint pain, namely 60-74 years old. Joint pain can interfere with activity. Joint pain management can solved by non-pharmacological methods such as progressive muscle relaxation therapy and finger gripping. This study aims to determine the effectiveness of a combination therapy of progressive muscle relaxation and finger gripping on joint pain in the elderly in the village of Kebonharjo. This is a quantitative study and quasi-experimental two-group pre-test and post-test control group design. The sampling technique used a random sampling of 20 respondents for the intervention group and 20 respondents for the control group. The research instrument used a questionnaire, a combination of therapies of progressive muscle relaxation and finger gripping with expert validity tests, and observation sheets. Data analysis using the Wilcoxon test and Mann-Whitney test. The results showed joint pain in the control group obtained a pre-value of 3.50 and post value of 4.00. Joint pain in the intervention group with a value of pre-4.00 and post-3.00. The results of the pretest of the control and intervention group obtained P-Value = 0.317 and P-Value <0.001. The posttest difference test between the control and intervention group is P-value = 0.003. The combination therapy of progressive muscle relaxation and finger gripping has been scientifically proven to reduce joint pain in the elderly in the village of Kebonharjo.